Inexpensive ionic liquids: [HSO]¯-based solvent production at bulk scale - Chen,L; Sharifzadeh,M; Mac,Dowell N; Welton,T; Shah,N; Hallett,JP (Green Chemistry, 2014)
Through more than two decades’ intensive research, ionic liquids (ILs) have exhibited significant potential in various areas of research at laboratory scales. This suggests that ILs-based industrial process development will attract increasing attention in the future. However, there is one core issue that stands in the way of commercialisation: the high cost of most laboratory-synthesized ILs will limit application to small-scale, specialized processes. In this work, we evaluate the economic feasibility of two ILs synthesized via acid–base neutralization using two scenarios for each: conventional and intensification processing. Based upon our initial models, we determined the cost price of each IL and compared the energy requirements of each process option. The cost prices of triethylammonium hydrogen sulfate and 1-methylimidazolium hydrogen sulfate are estimated as $1.24 kg−1 and $2.96–5.88 kg−1, respectively. This compares favourably with organic solvents such as acetone or ethyl acetate, which sell for $1.30–$1.40 kg−1. Moreover, the raw materials contribute the overwhelming majority of this cost and the intensified process using a compact plate reactor is more economical due to lower energy requirements. These results indicate that ionic liquids are not necessarily expensive, and therefore large-scale IL-based processes can become a commercial reality.